Cytomegalovirus sero-positivity dramatically alters the maternal CD8+ T cell repertoire and leads to the accumulation of highly differentiated memory cells during human pregnancy. (7th June 2011) - Lissauer, D; Choudhary, M; Pachnio, A; Goodyear, O; Moss, P A H; Kilby, M D
Abstract : During human pregnancy an allogeneic fetus is accommodated within an immunocompetent host. Human cytomegalovirus (CMV) infection during pregnancy can cause significant fetal disease. The balance between maternal immune competence, fetal tolerance and viral pathogenicity is thus delicately poised. We studied the CD8+ T cell (CTL) repertoire and CMV-specific T cell dynamics during healthy pregnancy and related this to CMV serostatus and gestation. Six human leucocyte antigen-peptide tetramers identified CMV-specific CTL. Phenotyping of CTL was carried out by 10 colour flow cytometry at a range of gestations (n=105). Serostatus was determined by CMV IgG ELISA. Maternal plasma levels of 27 cytokines were quantified by luminex assay. There was a significant reduction in naïve T cells in CMV seropositive women (21% vs 48%, p≤0.001) whereas the memory pool was markedly expanded with significantly more highly differentiated (CD45RA+CCR7-) CTL (34% vs 16%, p≤0.001). Seropositive women in the third trimester showed a significant increase in highly differentiated CTL (CD45RA+CCR7-) compared to the second trimester, which was not observed in seronegative women and was due to CMV specific CTL. CMV seropositivity had a marked impact on maternal CTL phenotype, with reduced naïve T cells and a more differentiated T cell phenotype. CMV seropositivity also altered the dynamics of the maternal immune response during pregnancy. Thus, CMV serostatus is a crucial confounder for studies of CTL during pregnancy. Also, reduced naive CTL may impair responses to other infections. The differentiated CTL repertoire and altered dynamics of the immunological response are likely to have a clinical impact on pregnancy.